(untitled) (Journal of Parents and Teachers, 2026)
Current issues and various proposals in education are analysed. Of particular note are the need to adapt school timetables to society, the lack of coherent educational projects, the importance of early childhood education and the effectiveness of practical learning, especially in vocational training.